Dignity in mental health care: human rights challenges and pathways - Robert Anders (Academia Mental Health & Well-Being)
This manuscript examines dignity in mental health care as a fundamental human right rather than a privilege. Despite the recognition of its importance, mental health systems often fail to uphold dignity in practice. This review explores theoretical frameworks underlying dignity, including capability approaches, rights-based perspectives, and care ethics, alongside international policy commitments that establish dignity as a cornerstone of mental health governance. The manuscript identifies key barriers to dignity-centered care—stigma, limited service access, and coercive practices—while highlighting promising innovations in digital mental health, trauma-informed approaches, and alternatives to coercion. Establishing dignity in mental health requires coordinated action across policy development, healthcare delivery, and community engagement, with particular emphasis on incorporating lived experience perspectives. Transforming mental health systems to prioritize dignity demands sustained investment, legal reform, and a fundamental shift toward approaches that recognize the inherent worth of every person regardless of their mental health status.